Silver Citrate Nanoparticles Inhibit PMA-Induced TNFα Expression via Deactivation of NF-κB Activity in Human Cancer Cell-Lines, MCF-7 - Abdellatif AAH; Rasheed Z; Alhowail AH; Alqasoumi A; Alsharidah M; Khan RA; Aljohani ASM; Aldubayan MA; Faisal W (International Journal of Nanomedicine, 2020)
Ahmed AH Abdellatif,1,2 Zafar Rasheed,3 Ahmad H Alhowail,4 Abdulmajeed Alqasoumi,5 Mansour Alsharidah,6 Riaz A Khan,7 Abdullah SM Aljohani,8 Maha A Aldubayan,4 Waleed Faisal9,10 1Department of Pharmaceutics, College of Pharmacy, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Al-Azhar University, Assiut 71524, Egypt; 3Department of Medical Biochemistry, College of Medicine, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 4Department of Pharmacology and Toxicology, College of Pharmacy, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 5Department of Pharmacy Practice, College of Pharmacy, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 6Department of Physiology, College of Medicine, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 7Department of Medicinal Chemistry and Pharmacognosy, College of Pharmacy, Qassim University, Buraydah 51452, Kingdom of Saudi Arabia; 8Department of Veterinary Medicine, College of Agriculture and Veterinary Medicine, Qassim University, Buraydah, Kingdom of Saudi Arabia; 9School of Pharmacy, University College Cork, Cork, Ireland; 10Faculty of Pharmacy, Minya University, Minya, EgyptCorrespondence: Ahmed AH AbdellatifCollege of Pharmacy, Qassim University, Buraydah 51452, Kingdom of Saudi ArabiaEmail a.abdellatif@qu.edu.saBackground: The nuclear factor kappa-B (NF-κB) is a major transcription factor responsible for the production of numerous inflammatory mediators, including the tumor necrosis factor (TNFα), which has a lethal association with cancer’s onset. The silver nanoparticles (AgNPs) are widely used in cancer treatment and several other biomedical applications.Objective: The study aimed to determine the effects of silver citrate nanoparticles (AgNPs-CIT) on NF-κB activation together with TNFα mRNA/protein expressions in the phorbol myristate acetate (PMA)-stimulated MCF-7 human breast cancer cell-lines.Methods: The AgNPs-CIT were synthesized by the reduction method, and the prepared AgNPs-CIT were characterized for their shape, absorption in UV-VIS electromagnetic radiations, size distribution, ζ-potential, and antioxidant activity. The MCF-7 cell-lines were pretreated with AgNPs-CIT and stimulated with PMA. The TNFα mRNA expressions were determined by real-time PCR, whereas the protein production was determined by the ELISA. The NF-κB activity was distinctly observed by highly-specific DNA-based ELISA, and by NF-κB-specific inhibitor, Bay 11– 7082.Results: The prepared AgNPs-CIT were spherical and have an absorption wavelength range of 381– 452 nm wherein the particles size ranged between 19.2± 0.1 to 220.77± 0.12 nm with the charge range − 9.99± 0.8 to − 34.63± 0.1 mV. The prepared AgNPs-CIT showed comparative antioxidant activity at > 40% inhibitions level of the DPPH radicals. The AgNPs-CIT were found to be non-toxic to MCF-7 cell-lines and inhibited PMA-induced activation of the NF-κBp65, and also the mRNA/protein expression of TNFα.Conclusion: This is the first report that showed AgNPs-CIT inhibited TNFα expression via deactivation of the NF-κB signaling event in stimulated breast cancer cells. The results have important implications for the development of novel therapeutic strategies for the prevention/treatment of cancers and/or inflammatory disorders.Keywords: phorbol myristate acetate, PMA, TNFα, NF-κB, silver citrate nanoparticles, MCF-7 cell lines, cancer, inflammatory cytokines